An Operational Conceptual Model for Global Communication Infrastructures - Aguiar, Rui L. (2009)
The global communication infrastructure has taken an increased relevance for the future global multimedia village. This global infrastructure has suffered from a mismatch between the conceptual models being used, and the effective operational networks deployed to support it. This mismatch is now affecting the much needed developments to support a global village. This paper presents a novel model for structuring communication networks which closely reflects the visions and needs from an operational network. This model shows a path for protocol evolutions for the global communication infrastructure.